Understanding the biochemical impact of leukoreduction on canine pRBC storage: a focus on reactive oxygen species and storage lesions - Shin, Sun Woo; Kim, Minji; Shin, Chaewon; Bae, Hyeona; Park, Jinho; Jung, Dong-In; Cho, Kyu-Woan; Yu, DoHyeon (Frontiers in Veterinary Science, 2025)
Transfusion therapy is vital for both humans and animals, though it poses significant risks, including the development of storage lesions in packed red blood cells (pRBCs). This study examines hematological and biochemical changes during the storage of canine pRBCs, focusing on intraerythrocytic reactive oxygen species (ROS) and the impact of pre-storage leukoreduction. Eleven pRBC units were each divided into two aliquots, resulting in a total of 22 units, eleven leukoreduced (LR-pRBC) and eleven non-leukoreduced (nLR-pRBC), which were analyzed over 42 days. Results showed increased hemolysis, lactic acidosis, and potassium efflux (All, p < 0.01), with more severe lesions in nLR-pRBCs due to leukocyte presence. Notably, intraerythrocytic ROS levels increased in both groups (p < 0.05), driven by hemoglobin autoxidation (p < 0.05), though they decreased in later storage stages due to hemolysis and membrane vesiculation. The study highlights that pre-storage leukoreduction mitigates storage lesions, suggesting its implementation to enhance pRBC storage safety. Further research is necessary to understand the role of antioxidant systems in controlling intraerythrocytic ROS and preventing storage lesions.